Implementasi Metode Permainan Susun Kata dan Susun Kalimat (Suka-Suka) untuk Meningkatkan Penguasaan Mufrodat Siswa Kelas X MA Darul Huda Gumukmas - BIN NAFSAH, NOR HOLIS; Kuni Hamidah (STAI Nurul Huda Kapongan Situbondo, 2024)
In learning a language, such as Arabic, mastery of mufrodat is the main key in supporting good language skills. However, for maximum results in mastering mufrodat, it is necessary to use the right method. And one method that can be realized is the